2020
DOI: 10.1002/jum.15483
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Survey Versus Fetal Echocardiograms for Diagnosis of Cardiac Defects with a Single Umbilical Artery Cases

Abstract: Objective To determine the utility of fetal echocardiography in diagnosing cardiac defects in fetuses with a single umbilical artery (SUA). Methods A retrospective cohort study of prenatally diagnosed SUA was conducted over a 10‐year period at a single institution. Cardiac anatomy on detailed anatomical survey was compared with fetal echocardiogram for fetuses with prenatally diagnosed SUA. A diagnostic meta‐analysis of studies comparing fetal anatomical survey to fetal echocardiogram in fetuses with SUA betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…We found 1384 studies by the search strategy used; after carefully reviewing the full‐text, we finally included 15 studies for analysis (Araujo Júnior et al, 2015; Chen et al, 2014; Chen et al, 2016; DeFigueiredo et al, 2010; Gossett et al, 2002; Gurram et al, 2018; Lee et al, 1998; Miller & Towner, 2019; Prefumo et al, 2010; Sun & Wang, 2018; Tasha et al, 2014; Tonismae et al, 2021; Vasanthalakshmi et al, 2012; Wang et al, 2019; Xin et al, 2014) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found 1384 studies by the search strategy used; after carefully reviewing the full‐text, we finally included 15 studies for analysis (Araujo Júnior et al, 2015; Chen et al, 2014; Chen et al, 2016; DeFigueiredo et al, 2010; Gossett et al, 2002; Gurram et al, 2018; Lee et al, 1998; Miller & Towner, 2019; Prefumo et al, 2010; Sun & Wang, 2018; Tasha et al, 2014; Tonismae et al, 2021; Vasanthalakshmi et al, 2012; Wang et al, 2019; Xin et al, 2014) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of cardiac disease in fetuses with SUA has been described as between 9% and 32% (Araujo Júnior et al, 2015; Friebe‐Hoffmann et al, 2019; Li et al, 2020; Tonismae et al, 2021). In our study, the incidence in fetuses with isolated SUA was 9%, like that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"The publication continues to justify the false belief that an ultrasound machine makes a diagnosis instead of the correct concept that ultrasound is just a piece of equipment that depends on the observer to make a correct diagnosis. 1 The authors do not seem to realize that "looks" normal versus "is" normal is a concept that depends on many factors including the expertise of the diagnostician. A diagnosis with a stethoscope in the hands of a cardiologist is vastly more valuable than letting a 5-year-old listen to a heart with the same stethoscope.…”
mentioning
confidence: 99%